2010
DOI: 10.1592/phco.30.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Risks for Cytomegalovirus Infection and Disease After Solid Organ Transplantation

Abstract: Cytomegalovirus continues to be one of the most clinically significant infections after solid organ transplantation. Classic definitions of patients at high risk for infection and tissue-invasive disease are focused on recipient-donor serostatus, type of organ transplanted, and overall level of immunosuppression. However, recent trends in clinical practice call for a reevaluation of cytomegalovirus infection risks after solid organ transplantation. Indeed, whereas early-onset cytomegalovirus infection is usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 120 publications
(161 reference statements)
0
10
0
Order By: Relevance
“…1 Patients at high risk for CMV replication and disease are seronegative individuals receiving an organ from a seropositive donor, or those receiving intensive and strongly T-cell-depleting immunosuppression, such as antithymocyte globulin (ATG). 2 Natural killer (NK) cells are of special interest in SOT, since studies have shown that these innate lymphocytes may be less susceptible to immunosuppressive agents such as calcineurin inhibitors. 3,4 In agreement with a role of NK cells in antiviral immunity after SOT, polymorphisms within the Killer cell Immunoglobulin-like Receptor (KIR) gene complex have been correlated with the risk of CMV replication after solid organ or hematopoietic stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Patients at high risk for CMV replication and disease are seronegative individuals receiving an organ from a seropositive donor, or those receiving intensive and strongly T-cell-depleting immunosuppression, such as antithymocyte globulin (ATG). 2 Natural killer (NK) cells are of special interest in SOT, since studies have shown that these innate lymphocytes may be less susceptible to immunosuppressive agents such as calcineurin inhibitors. 3,4 In agreement with a role of NK cells in antiviral immunity after SOT, polymorphisms within the Killer cell Immunoglobulin-like Receptor (KIR) gene complex have been correlated with the risk of CMV replication after solid organ or hematopoietic stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In kidney recipients, CMV is associated with direct effects, including CMV infection, disease, and end‐organ damage affecting the transplanted allograft, as well as indirect effects such as increased risk of rejection, Epstein–Barr virus‐associated post transplant lymphoproliferative disorder (PTLD), opportunistic infection, and malignancy . Risk factors for CMV infection include the net state of immunosuppression, the type of organ transplant, and donor/recipient serostatus . Given the significant risk for CMV‐related complications post transplant, universal prophylaxis is recommended for all high‐risk patients .…”
mentioning
confidence: 99%
“…Although primarily used for induction therapy, some agents have also been used in maintenance immunosuppression in some centers (Table ). They are, however, associated with an increased risk of infection, including cytomegalovirus (CMV) infection, and post‐transplant lymphoproliferative disorder (PTLD) . In addition, biologic agents based on non‐human proteins, such as OKT3, may induce antibody formation that limits their effectiveness .…”
Section: New Biologic Immunosuppressive Agents Are Being Developed Tomentioning
confidence: 99%